Pengaruh Perbedaan Temperatur Cetakan Logam Terhadap Fluiditas dan Struktur Mikro MG-44%AL - Amir Arifin (Universitas Sriwijaya, 2009)
Lenght of fluidity is one of important factor that give influence on thin wall casting. The increasing lenght of fluidity will increase feeding ability molten metal. At the thin wall mould, the cooling rate temperature move rapidly and then increasing solidification rate cast metal. The aim of the research is studiying optimal mould temperature on Mg-44%Al casting process. Gravity methode is used as this casting. The mould was made by machining process. Molten metal was pouring on 650oC, 700 oC and 750 oC into difference mould temperature (650oC, 700oC and 750 oC). The mould has difference thickness 0,5 mm; 1mm; 1,5 mm; 2 mm; 2,5 mm; 3 mm; 3,5 mm;dan 4 mm. The maximum length of fluidity at mould temperature 200oC on pouring temperature 700oC. Each of mould temperature, Increasing lenght of fluidity untill mould temprature 650oC and 700oC but decreasing lenght of fluidity after pouring temperatur 750oC, at all difference mould temperatures.